Digitizing the Informed Consent Process: A Review of the Regulatory Landscape in the European Union - De Sutter, Evelien; Meszaros, Janos; Borry, Pascal; Huys, Isabelle (Frontiers in Medicine, 2022)
Background: Rapid technological advancements are reshaping the conduct of clinical research. Electronic informed consent (eIC) is one of these novel advancements, allowing to interactively convey research-related information to participants and obtain their consent. The COVID-19 pandemic highlighted the importance of establishing a digital, long-distance relationship between research participants and researchers. However, the regulatory landscape in the European Union (EU) is diverse, posing a legal challenge to implement eIC in clinical research. Therefore, this study takes the necessary steps forward by providing an overview of the current regulatory framework in the EU, relevant to eIC. Methods: We reviewed and analyzed the key EU regulations, such as the EU General Data Protection Regulation (GDPR) and the Clinical Trials Regulation (CTR). We investigated the legality of eIC in several EU Member States, Switzerland, and the United Kingdom. To this end, we contacted the medicines agencies of various countries to clarify the national requirements related to the implementation and use of eIC in clinical research. Our research was complemented by comparing the legal acceptance of eIC between the EU and the United States. Results: In the EU, a distinction must be made between eIC for participation in clinical research and eIC for processing the participants’ personal data, complying respectively with requirements laid down by the CTR and the GDPR. On a national level, countries were classified into three groups: 1) countries accepting and regulating the use of eIC, 2) countries accepting the use of eIC without explicitly regulating it, and 3) countries not accepting the use of eIC. As a result, the regulation of eIC through laws and guidelines shows a large variety among EU Member States, while in the United States, it is harmonized through the Code of Federal Regulations. Conclusion: Various requirements must be considered when implementing eIC in clinical research. Nevertheless, requirements across the EU Member States may differ significantly, whereas, in the United States, efforts have already been made to achieve a harmonized approach.